Influence of Bariatric Surgery on Salivary Flow: a Systematic Review and Meta-Analysis - Farias, Tatyana M. C. P.; Vasconcelos, Belmiro C. do E.; SoutoMaior, Juliana R.; Lemos, Cleidiel A. A. [UNESP]; de Moraes, Sandra L. D.; Pellizzer, Eduardo P. [UNESP] (Springer Nature, 2019)
Bariatric surgery is the most effective treatment for morbid obesity, but it can cause numerous adverse effects. This systematic review and meta-analysis aimed to evaluate whether bariatric surgery changes patient salivary flow. We searched for articles in the Web of Science, Pubmed/MEDLINE, and Scopus databases using the search terms “oral health AND bariatric surgery OR gastrectomy OR obesity surgery.” We recovered 845 articles. After the removal of duplicates and exclusions, eight studies remained. Of them, five showed no significant difference in salivary flow values, two showed an increase in flow rate, and one showed a reduction in flow rate (p < 0.05). The results of the included studies showed no significant alteration in salivary flow rate for up to 24 months after bariatric surgery.
Keywords: Bariatric surgery; Gastrectomy; Obesity surgery; Oral health; salivary flow